Exploring factors hindering the uptake of HIV pre-exposure prophylaxis by potential users in Namibia - Daniel O. Ashipala (AOSIS, 2024)
Background: Pre-exposure prophylaxis (PrEP) is recommended for people who are at substantial risk of HIV infection, in conjunction with other HIV prevention tools and strategies. Unfortunately, the uptake of PrEP among potential users in Namibia's Okongo district is low. Objectives: The objective of this study was to explore and describe the factors that hinder the uptake of HIV PrEP by potential users at the Okongo District Hospital in Namibia. Method: A qualitative exploratory, descriptive and contextual design was used. The study sought to understand the factors hindering uptake of HIV PrEP by potential users in the peri-urban setting of Okongo District Hospital, Namibia. Purposive sampling was used to select participants for this study, with qualitative data being gathered from semi-structured interviews with 20 potential PrEP users. The data were analysed using qualitative thematic analysis. Results: Participants reported numerous factors hindering uptake, including level of understanding, non-compliance on the part of the health department, distances, and attitudes. Additionally, participants maintained that health workers do not put enough effort into educating patients in the different hospital departments about PrEP, and sometimes there is insufficient stock of the medicine, both of which hinder PrEP uptake. Conclusion: Despite the PrEP rollout, multiple obstacles continue to hinder PrEP uptake, especially in the outskirts of Okongo district. This study recognises that there is a need to work hand in hand with the support systems of both potential users.